Blue Key (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Remote Controlling already exists in our daily life and is not a new concept. But here we came with a new technology in the controlling system. We are going to use our mobile for this purpose. As mobile is a very common device that every person carries all the time. Taking the advantage of this phenomenon; we are going to use this as remote for controlling home doors increasing the luxury of life with some added advantages. What is more natural than using a key to unlock a door? It is something that everyone does almost every day, and it is an integrated part of our daily life. It is also a very well-known and well-tested technology. Despite these arguments, keys as we know them might not be the device of choice to open doors in the future. We have all experienced problems like carrying too many keys while forgetting the one key we need, or maybe having a lock replaced because we lost a single key.